Preloved Reviewed from the Perspective of Maslahah Mursalah - Siti Nurhasanah; Shalsa Sri Wulandari; Jaenudin J; Dian Herdiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the practice of preloved goods trading from the perspective of maslahah mursalah and maqasid al-shariah, focusing on its economic, social, and environmental benefits. This research uses a qualitative method with a normative-empirical approach through interviews with preloved business actors in the local area. The results show that preloved trading activities provide various forms of public benefit, including economic efficiency, social equity, and environmental sustainability. Economically, it helps society manage expenses and creates new business opportunities. Socially, preloved promotes solidarity and reduces consumption inequality among different economic classes. Environmentally, it contributes to reducing textile waste and supports the sustainable fashion movement. In Islamic legal perspective, preloved trading is a lawful (mubah) transaction aligned with maqasid al-shariah, as it involves no elements of riba, gharar, or tadlis and delivers benefits to the wider community. Therefore, the preloved trade can be regarded as an embodiment of maslahah mursalah values in the context of contemporary Islamic economics